(untitled) (Journal of Universal Science Research, 2023)
This article is about the study of professional orientation of FL teaching in the linguo-didactic aspect is designed to strengthen the general knowledge of FL (grammar, vocabulary, phonetics, syntax) acquired before entering the university, supplementing them with lexical and grammatical knowledge.